Knowledge of Premarital Screening among Prospective Brides and Grooms as a Determinant of Visits to Healthcare Facilities - Centis, Maria Conchita Leyla; Dewi, Imelda Rosniyati; Bandur, Paskalinda Maria Yosefa (Jurnal Penelitian Kesehatan SUARA FORIKES, 2026)
Premarital screening constitutes a preventive strategy aimed at the early detection of potential health problems that may affect marital life and future offspring. The level of knowledge among prospective brides and grooms regarding the importance of premarital screening is presumed to influence their healthcare-seeking behavior, particularly visits to healthcare facilities. This study aimed to examine the relationship between the level of knowledge of prospective brides and grooms about premarital screening and their visits to healthcare facilities. A quantitative study with a cross-sectional design was conducted. The sampling technique employed was non-probability sampling using a total sampling approach. Data were collected using a structured questionnaire as the research instrument. Statistical analysis was performed using the Chi-square test to determine the association between knowledge level and healthcare facility visits. The findings revealed a significant relationship between the knowledge of prospective brides and grooms regarding premarital screening and their visits to healthcare facilities (p-value < 0.001). As conclusion, knowledge of premarital screening among prospective brides and grooms is determinat of healthcare facility visitation behavior. Broader educational interventions are necessary to enhance knowledge and awareness regarding premarital screening in order to promote the establishment of healthy families.Keywords: knowledge; prospective brides and grooms; premarital screening; healthcare visits; healthcare facilities